KARAKTERISTIK SISTEM GASIFIKASI TYPE DOWDRAFT GASIFIER BERBAHAN BAKAR BIOMASSA BERDASARKAN VARIASI VOLUME RUANG BAKAR - Elfiano, Eddy; Suripto, Heri; Hastuti, Kurnia; Arizona, Rafil; Lihantoro, Bayu (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
This research aims to investigate the attributes of a Downdraft Gasifier gasification system that employs biomass fuel and features varying combustion chamber capacities. The primary focus is on examining how alterations in combustion chamber volumes affect gasification characteristics. Analytical techniques that hinge on these discrepancies in combustion chamber capacities yield a comprehensive understanding of efficiency, thermal functionality, and gas discharges. The outcomes suggest that the gasification setup furnishes adequate thermal energy for highly efficient catfish drying. Additionally, the application of gasification diminishes noxious discharges from the exhaust, thereby establishing a more eco-friendly technology. The most efficient utilization of energy is apparent in rice husks, accounting for operational duration, steam generation, and assessments of performance parameters. As per gas emission analyses, wood powder demonstrates reduced emissions compared to rice husks, particularly concerning CO2, CO, SO2, NO, and NOX emissions throughout the gasification process.